Trends in Microencapsulation of Lemuru Fish Oil for Child Nutrition: A Systematic Review of Oxidative Stability, Sensory Acceptance, and Fortification Opportunities in Cereal Products - Rozi, Moh Fatkhur; Swasono, Muh Aniar Hari (Jurnal Penelitian Multidisiplin Bangsa, 2026)
Lemuru fish oil, rich in long-chain polyunsaturated fatty acids like EPA and DHA, is vital for children's growth and brain development. However, its chemical instability complicates its incorporation into food products. This review, adhering to PRISMA 2020 guidelines, analyzes microencapsulation technology for fish oil, focusing on preserving quality and flavor when added to foods such as cereals for young children. A search of Scopus and Elsevier yielded 19 relevant papers from 2015 to 2025. Various microencapsulation methods and coating materials were examined, revealing that complex coacervation with chitosan and proteins (encapsulation efficiency of 87-93%) and spray-drying techniques offer superior protection against oxidation. Taste studies suggest that incorporating fruit flavors and antioxidants mitigates the fishy flavor, enhancing consumer acceptance. Furthermore, microencapsulated Lemuru fish oil shows improved performance in digestion simulations, supporting its role in child nutrition programs. The review also points out gaps for future research to enhance microencapsulation for effective fortified cereals, especially in omega-3 deficient regions.